A review on the medicinal chemistry of sodium glucose co-transporter 2 inhibitors (SGLT2-I): Update from 2010 to present - Jonali Ramani; Harshil Shah; Vivek K. Vyas; Manmohan Sharma (Elsevier, 2022)
Diabetes mellitus (DM) is one of the leading causes of death by World Health Organization in 2019 and is considered a significant cause of other diseases including heart attack, stroke, kidney failure, blindness, and lower limb amputation. Sodium glucose co-transporter 2 (SGLT2) is a protein that reabsorbs around 90% of glucose from plasma glucose. SGLT2 is a recognised target for the treatment and management of diabetes. SGLT2 inhibitors (SGLT2-I) have entered in the market for managing glucose levels in diabetes. There are six SGLT proteins in the human body varying in their preference for sugar binding. The therapeutic approach focuses on the SGLT2 located in the intestine and early proximal tubule of the nephron that facilitates glucose reabsorption by approximately 90%. The expression of SGLT2, and tubular glucose load increases in the diabetic condition and hence the glucose reabsorption leads to hyperglycemia. SGLT2-I functions by inhibiting the reabsorption of glucose from renal tubule and enhancing the glucose excretion via urine. Discovery and development of selective SGLT2-I have a great potential for the treatment and maintenance of diabetes mellitus. This review provides an understanding of medicinal chemistry approaches toward the discovery of novel SGLT2-I over a decade. Compiled studies will help to describe the safety, efficacy, and benefits of various SGLT2-I in the management of blood glucose in diabetic patients.